PERISTILAHAN BETUNANG DALAM MASYARAKAT KAYAAN MENDALAM PUTUSSIBAU - Pratiwi, Felissiana Bella (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract         Kayaan Mendalam Putussibau community is a group of Dayak communities living in the interior of West Kalimantan Putussibau exactly in the northern part, people Kayaan Mendalam still adhere to the culture one is the engagement of indigenous culture. in a custom engagement, there are three stages: ake anaak, pehengkung Daho ', and betunang. This study focused on the semantic field that terminology in the indigenous community engagement Kayaan Mendalam Putussibau. The general problem is limited to two subproblems, namely the description terminolog, and type of meaning. The method used in this study is a survey method, observation, and interviews with qualitative terms .Data in this study are objects, food and traditional forms of engagement procession requirements. The technique used in this study were interviews and direct conversations. Based on the analysis found some sort of meaning contained in the study 43 and 10 lexical meaning of cultural meaning. Data terminology indigenous engagement by Ake Anaak stage found many as 13 terms, divided in 4 terminology requirements, 4 terminology tools, terminology and 5 food names. At stage of Pehengkung Daho 'there are 14 terms consisting of 3 terminology requirements, 9 terminology tool and the second name of the food. At stage of betunang found 23 terms, divided in 3 terminology requirements, 10 terminology tools, terminology and 10 food names.  Keywords: Terminology, Betunang, and Kayaan Mendalam Putussibau.